The effect of health education on knowledge and attitudes about cesarean in Tehrani women - Asfia, Abolghasem; Azam, Kamal; Babaei Heydarabadi, Akbar; Gilasi, Hamid Reza; Ghanei, Zahra; Dariyani, AliReza; Karbalaei, Zohreh; Normabodi, Hilda (Advances in Nursing & Midwifery, 2013)
Abstract: Background: More than 70 percent of pregnant women in Iran demand unnecessary cesarean. Although just 15% of cesarean sections required to intervention. Also, according to World Health Organization, acceptable cesarean rate can be up to 15%. Materials and Methods: This study is an intervention type before and after that on 64 pregnant women referred to health centers in areas 16 and 17 in Tehran in 2010. First, knowledge and attitude was assessed by questionnaire and then the intervention was conducted. The intervention was included education lectures and an educational pamphlet. Knowledge and attitude was assessed after 2 weeks by the same questionnaire. After collecting the data were analyzed using statistical software SPSS-16. Results: Mean age was 26±5/45 years and 75 and 73.4 percent of them were women and their spouses in order to graduate with a degree of guidance. Jobs more than 95 percent of them were housewives and 50% of their husbands were worker. 31% of them were unwanted pregnancy. Average score of knowledge about training before 46/6±5/7 and after the educational intervention was 54±5/86. This increase is statistically significant. The attitude scores of women before and after the educational intervention was 47/6±7/4 and 49/5 ±5/8, respectively, but this increase was not statistically significant. Conclusion: Management of training courses beside interventional procedures based on theories and models of health education and health promotion will be effective step in reducing the cesarean rate as well as promoting the level of health mothers and their children. Keywords: Knowledge, attitude, educational intervention, cesarean